Sektor Unggulan Kabupaten Tulungagung dan Perannya Terhadap Penyerapan Tenaga Kerja - Gayatri Tirta Lesmana Putri; Hendry Cahyono (Jurnal Ekonomika : INDEPENDEN, 2021)
The successful regional economic development can be measured from the level of economic growth through PDRB indicators. The attainment is done through the determination and development of the leading sector that can influence the rate of labor absorption onward. The purpose of this study to analyze the leading sectors of Tulungagung Regency and their roles in labor absorption. The successful regional economic development can be measured from the system of leading sector towards the absorption of labor and has to decreased of unemployment rate. The researcher made use of descriptive analysis through a mathematical approach, using combined LQ-DLQ analysis, shift-share, Klassen typology, and overlay analysis. The findings demonstrate that the communication and transportation sectors were Tulungagung Regency’s leading sectors 2014-2018, and economic structural change happened. The economy that depended on secondary and tertiary sectors illustrate that Tulungagung Regency did not rely on the exploitation of natural resources. On the other hand, the role of the leading sector on labor absorption is inelastic and has not to decreased unemployment.